2020
DOI: 10.1002/lary.28550
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Salvage Therapy in Isolated Regional Recurrence in Head and Neck Squamous Cell Carcinoma

Abstract: Objectives/Hypothesis Head and neck squamous cell carcinoma (HNSCC) has a high tendency for regional lymphatic spreading. Nevertheless, isolated regional lymph node recurrences are rare, and only limited data regarding its management are available. The aim of this study was to describe treatment modalities and outcomes, and to identify prognostic factors. Study Design Retrospective cohort study. Methods The records of all patients (n = 498) with tumor persistence or recurrence after curatively intended treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…Our results are in accordance with the recent literature 24–26 . Giger et al 25 reported advanced rcN stage in up to 60% of isolated neck recurrences, despite there being 56.6% of cN0 detection at the primary tumor diagnosis; a mean interval of 18.1 months was observed between initial tumor treatment and histological/cytological diagnosis of the IRR.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in accordance with the recent literature 24–26 . Giger et al 25 reported advanced rcN stage in up to 60% of isolated neck recurrences, despite there being 56.6% of cN0 detection at the primary tumor diagnosis; a mean interval of 18.1 months was observed between initial tumor treatment and histological/cytological diagnosis of the IRR.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with the recent literature 24–26 . Giger et al 25 reported advanced rcN stage in up to 60% of isolated neck recurrences, despite there being 56.6% of cN0 detection at the primary tumor diagnosis; a mean interval of 18.1 months was observed between initial tumor treatment and histological/cytological diagnosis of the IRR. Similarly, Léon et al 24 previously recorded rcN2/3 in 97 of 123 IRRs (78.86%) with 66.7% of ENE+, even though no regional involvement of primary tumor was detected in 60.98% of cases; moreover, those authors did not find any relationship between the presence of nodes with extracapsular spread and the local or regional extension of the primary tumor, the initial therapy, or time to regional recurrence on multivariate analysis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The reported overall survival outcome for isolated nodal recurrence treated with salvage neck dissection varies from 25 per cent to 56 per cent. 1104,1105 Favourable prognostic factors for survival include p16-positive SCC, complete margins, no extra-nodal extension, low-volume disease, no previous neck treatment and a disease-free interval of greater than six months. 1106 Current evidence suggests regional recurrence occurs generally in the previously treated involved neck levels, regardless of whether the initial modality was surgery or (chemo)radiotherapy.…”
Section: Recommendationsmentioning
confidence: 99%